Implementation of REDD+ Activities in North-Eastern States of India: A Case Study from The State of Mizoram - Rawat, R. S.; Arora, Gurveen; Rawat, V. R. S. (Indian Forester, 2019)
Role of forests is well recognised as low-cost carbon mitigation option along with significant co-benefits. REDD+ is one of the climate change mitigation option in developing countries relating to reducing emissions from deforestation and forest degradation, role of conservation, sustainable management of forests and enhancement of forest carbon stocks. Implementation of REDD+ Himalaya Project was focused in North- Eastern states of India whereas Mamit District of Mizoram was chosen as REDD+ pilot project site for implementation of various field activities under the project. Shifting cultivation, fuel wood collection and over exploitation of non-wood forest products were identified as major direct drivers whereas lack of sufficient employment opportunities and awareness were identified as major indirect drivers of deforestation and forest degradation. These identified drivers were also responsible for loss of biodiversity. Strategies were also identified to address the drivers of deforestation and forest degradation. Feasibility study showed that implementation of activities such as promotion of agroforestry, shaded coffee plantation, use of improved cook stoves and solar energy etc. can address the drivers of deforestation and forest degradation which will also provide carbon and non-carbon benefits to the local communities. A total forest carbon stock of 2916 million tonnes was estimated from the pilot project site. State REDD+ Action Plan has also been prepared to support implementation of National REDD+ Strategy and will also be helpful in obtaining result based payment and other social and environmental co-benefits for the state of Mizoram.